2012
DOI: 10.1371/journal.pone.0041915
|View full text |Cite
|
Sign up to set email alerts
|

Thermotaxis of Human Sperm Cells in Extraordinarily Shallow Temperature Gradients Over a Wide Range

Abstract: On the basis of the finding that capacitated (ready to fertilize) rabbit and human spermatozoa swim towards warmer temperatures by directing their movement along a temperature gradient, sperm thermotaxis has been proposed to be one of the processes guiding these spermatozoa to the fertilization site. Although the molecular mechanism underlying sperm thermotaxis is gradually being revealed, basic questions related to this process are still open. Here, employing human spermatozoa, we addressed the questions of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
58
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 35 publications
6
58
1
Order By: Relevance
“…The temperature of the female reproductive system plays a significant role of determining the sperms movement direction. The scientists found that the sperm head acts like a temperature sensor to search for a warmer area (the egg location) [28]. Furthermore, the sperm head can response and sense to a temperature difference of <0.0006 °C [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature of the female reproductive system plays a significant role of determining the sperms movement direction. The scientists found that the sperm head acts like a temperature sensor to search for a warmer area (the egg location) [28]. Furthermore, the sperm head can response and sense to a temperature difference of <0.0006 °C [28].…”
Section: Introductionmentioning
confidence: 99%
“…As we mentioned previously, sperm head acts like a temperature sensor, which prefers to swim towards warmer temperatures (egg location) [28]. In addition, sperm moves forward to search on the guidance (higher concentrations of molecules) that produced and released by the egg, which this guidance knew as Chemo-taxis [31].…”
mentioning
confidence: 97%
“…4 Recently, they used a Lucite tube device with a controllable temperature gradient to show that only a small fraction of human sperm, which are capacitated and ready-tofertilize, have thermotactic responses, and that portion of sperm can respond to both ascending and descending temperature gradient within a wide temperature range. 5,6 Despite these advances, a convenient and efficient observable device with precise control of temperature gradient is still need to be developed for human sperm thermotaxis screening.…”
Section: Introductionmentioning
confidence: 99%
“…These findings raised the hypothesis that the temperature difference might serve as a cue for guiding spermatozoa to the site of fertilization. Interestingly, Bahat et al,(10) recently has reported that human spermatozoa are thermotactically responsive over a wide temperature range (29-41 ℃), much wider than the range considered physiological.As in sperm chemotaxis, only capacitated spermatozoa are thermotactically responsive (9). Additionally, in chemotaxis and thermotaxis, spermatozoa swim up the gradient by modulating the frequency of turns and hyperactivation events, essentially in the direction of the gradient (11,12).…”
mentioning
confidence: 99%
“…These findings raised the hypothesis that the temperature difference might serve as a cue for guiding spermatozoa to the site of fertilization. Interestingly, Bahat et al, (10) recently has reported that human spermatozoa are thermotactically responsive over a wide temperature range (29-41 ℃), much wider than the range considered physiological.…”
mentioning
confidence: 99%